(untitled) (Journal of Fiber Bioengineering and Informatics, 2022)
In order to meet the needs of consumers for the fit of bra and solve the problems in the production process of mold cup, this paper proposed a forward grading design method based on the idea of personalized customization. This paper analyzes the feature points of the human body and the mold cup to find the relationship between the human body characteristics and the mold cup control parameters, and establishes a quantitative formula for the constraint relationship between the basic mold cup and the functional mold cup based on the human body, and passes UG OPEN GRIP programs the generation process of the inner surface of the mold cup in UG, and realizes the automatic generation of the functional mold cup by controlling the design parameters in the UG environment. And discuss the application of the parameterized design model of the inner surface of the personalized custom middle mold cup, including: the application for individuals with different human body data and the application of selecting different functional parameter values for the same human body data. This method provides a method reference for the digital design method of mold cups in the future.